Wind Energy Management - Bhattacharya, Paritosh (IntechOpen, 2011)
The book "Wind Energy Management" is a required part of pursuing research work in the field of Renewable Energy at most universities. It provides in-depth knowledge to the subject for the beginners and stimulates further interest in the topic. The salient features of this book include: - Strong coverage of key topics - User friendly and accessible presentation to make learning interesting as much as possible - Its approach is explanatory and language is lucid and communicable - Recent research papers are incorporated